Shortell and Kaluzny's health care management : organization design and behavior - Bradley, Elizabeth H.; Bradley, Elizabeth H.;Weiner, Bryan Jeffrey (Australia : Delmar Cengage Learning, 2012)
This books is intended for those interested in a systematic understanding of organizational principles, practices, and insights pertinent to the management of health services organizations.
PART ONE Introduction -- PART TWO Micro Perspectives -- PART THREE Macro Perspectives.
Includes bibliographical references and index.
Keywords: HEALTH SERVICES ADMINISTRATION